An energy consumption minimization approach in wireless sensor networks - Muhsin J. Al-Amery; Mohammed H. Ghadban (Institute of Advanced Engineering and Science, 2021)
There is no doubt that the most challenging aspect in the wireless sensor networks (WSN) is the lifetime, due to limitations in their energy. WSN depends on a specific group of sensor nodes to gather the data from other nodes and forward it to the base station (BS). These nodes are called cluster heads. Having reliable cluster head’s (CH) means longer life to the network. In this paper, a versatile calculation has been acquainted and analyzed for selecting the CH that maintains the least vitality utilization in the network with appropriate life time during every correspondence round. The altered methodology depends on the improved calendar of the time division multiple access (TDMA) plans. This methodology is created to decide the next CH based on lifetime, expended vitality, number of CH’s, and the frequent contact to the BS. A comparative analysis is introduced, the proposed algorithm assistant cluster heads (ACHS) shows energizing outcomes in vitality utilization in WSNs just as expanding the general system dependability with reasonable viability and productivity in terms of lifetime. The ACHS strategy shows a decrease in the WSN vitality utilization up to about 25% and shows an expansion in the system life time by 30% than the upgraded timetable of time TDMA plan approach.